PENGUATAN KAPASITAS PELAKU WISATA DAN UMKM MELALUI PELATIHAN GREEN TOURISM DI KAWASAN BOROBUDUR - Al Anshori, Hannif Andy; Alif Fahmi Rizki, Galuh; Tri Widayati, Maria; Nurasa, Heru; Nugraha, Awaludin (Universitas Padjadjaran, 2026)
The Borobudur area, as a super-priority destination, has considerable potential to serve as a model for community-based green tourism management. However, micro, small, and medium-sized enterprises (MSMEs) and tourism business groups in the area still require capacity strengthening to implement sustainability principles and environmentally friendly business practices. This community engagement program aimed to enhance the competencies of tourism-related MSMEs through a Training of Beneficiaries on Green Tourism MSMEs. The training focused on financial literacy, marketing strategies, and the internalization of green tourism values. The program was designed using Adult Learning (andragogy) principles and the Experiential Learning Cycle (ELC). It employed participatory, experiential learning strategies, emphasizing active engagement through practical reflection, group discussions, case studies, role-playing activities, and follow-up action planning. Pre-test and post-test evaluations showed a significant improvement in participants’ understanding. The average score increased from 61.34 to 85.66, with an N-Gain of 0.55, indicating a moderately effective effect size. Beyond knowledge enhancement, participants showed positive shifts in attitudes toward business sustainability, improved financial management, and the emergence of collaboration and environmentally oriented product innovation. Overall, the program was effective in strengthening the capacity and awareness of tourism MSMEs in the Borobudur area to adopt more sustainable green business practices.Kawasan Borobudur sebagai destinasi super prioritas memiliki peluang besar untuk menjadi contoh pengelolaan pariwisata hijau berbasis komunitas. Namun, pelaku usaha mikro, kecil, dan menengah (UMKM) serta kelompok usaha wisata di kawasan ini masih membutuhkan penguatan kapasitas untuk menerapkan prinsip keberlanjutan dan praktik usaha ramah lingkungan. Program pengabdian ini bertujuan meningkatkan kompetensi pelaku usaha melalui pelatihan Training of Beneficiaries on Green Tourism MSMEs yang berfokus pada literasi keuangan, strategi pemasaran, dan internalisasi nilai-nilai pariwisata hijau (green tourism). Pelatihan dirancang menggunakan prinsip Pembelajaran Orang Dewasa (andragogi) dan Experiential Learning Cycle (ELC), dengan strategi partisipatif berbasis pengalaman yang menekankan keterlibatan aktif peserta melalui refleksi praktik, diskusi, studi kasus, bermain peran, dan perencanaan tindak lanjut. Evaluasi pretest dan post-test menunjukkan peningkatan pemahaman peserta secara signifikan, ditandai kenaikan nilai rata-rata dari 61,34 menjadi 85,66 dengan skor N-Gain 0,55 (kategori efektivitas sedang). Selain peningkatan pengetahuan, peserta menunjukkan perubahan sikap terhadap keberlanjutan usaha, perbaikan kemampuan manajemen keuangan, serta munculnya kolaborasi dan inovasi produk berbasis lingkungan. Secara keseluruhan, program ini efektif membangun kapasitas dan kesadaran UMKM pariwisata di kawasan Borobudur untuk mengadopsi praktik bisnis hijau yang lebih berkelanjutan.